Black middle class Britannia : identities, repertoires, cultural consumption - Meghji, Ali (Racism, resistance and social change., 2019)
This book analyses how racism and anti-racism affects Black British middle class cultural consumption, incorporating insights from critical race theory and cultural sociology.